(untitled) (International Journal of Environmental Sciences, 2025)
This study focuses on determining the chromatic numbers of the fuzzy middle graph, fuzzy splitting graph, fuzzy shadow graph, fuzzy line graph, total fuzzy graph and fuzzy subdivision graph of the fuzzy cycle . These results are obtained by using fuzzy colors based on the strength of edges incident on a vertex. Additionally, some key properties regarding the fuzzy coloring of the fuzzy graphs have been given.